Podwojony dialog — przekładu i twórczości własnej — ujęcie komparatystyczne? - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2014)
Doubled dialogue of the translation and own artistic work — comparative perspective? The subject of this article is concerning the area of translation created by an author, a writer. In such case not only the dialogue between poetics of an author’s primary texts and the poetics of self-translated texts is at importance. The relation in which particular translation is involved with the original author’s passages also cannot be diminished. Those problems open a wide space for the translation and comparative studies research. The translation is perceived as an interpretation seen accordingly to the postulates of modern comparative studies — so as an intercultural dialogue, the dialogue of literature, opening itself for further relations in the sphere of ultimate culture and the own artwork of the author of the translation. In Poland it applies to works (original and translational) of — among others — Stanisław Barańczak, Julian Tuwim or Czesław Miłosz. In reference to the translations of Slovenian literature in Poland and Polish literature in Slovenia (after year 1990) one of the fascinating phenomenon in this context would be mutual translation of their own texts of two poets — Adam Wiedemann and Primož Čučnik. Their translations function as a complement rather than polemic factor. The authors explicitly point to initiating the intertextual relations between their texts. The resemblance of the poetics and choices made in the scope of translation unveil the relationship in terms of an idea, outlook on the world and aesthetics. Key words: literary translation, comparative study, Adam Wiedemann, Primož Čučnik, dialogism